DESIGNING â€œLISTEN TO ME GAMEâ€ AS LISTENING MATERIAL TO SUPPORT THE LEARNING OF DESCRIBING PEOPLE SUBJECT - Pratiwi, Anggun; ., Ikhsanudin; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The focus of this research is to design Android application game as a tool to support the students in listening comprehension. This research was conducted on the class A seventh grade students of MTsN 1 Pontianak. The method of this research is development research which consist of five phases; analysis, design, develop, implement and evaluation or called ADDIE. This material was designed as supplementary material to support listening comprehension in describing people. In this research found that listen to me game can support listening comprehension in describing people for seventh grade students of MTs N 1 Pontianak. This research uses design phase to determine the learner role, teacher role, instructional media role and prepare some material such as picture, audio, and game maker studio program to create the application. In the development phase, the researcher creates the application from the material that already gathered from design phase. To try out and see the usability of the product the researcher uses implementation phase. The result of evaluation phase is 4.64, it showed that the game is feasible to be used by students as supplementary material to support listening comprehension in describing people. Key words: Development Research, Listening Material, Designing Material Abstrak: Penelitian ini fokus untuk mendesign aplikasi game di Android sebagai materi listening untuk membantu siswa pada materi pembelajaran describing people. Penelitian ini diadakan di kelas 7A MTs N 1 Pontianak. Metode penelitian ini adalah development research yang terdiri dari 5 fase yaitu: Analisis, desain, pengembangan, implement dan evaluasi atau disebut ADDIE. Dalam penelitian ini ditemukan bahwa listen to me game dapat digunaka untuk materi describing people untuk siswa kelas 7 MTs N 1 Pontianak. Penelitian ini menggunakan tahap design untuk menentukan peran siswa, peran guru dan peran media pembelajaran dan menyiapkan beberapa bahan ajar seperti gambar, audio dan aplikasi game maker studio untuk membuat game di Android. Pada tahap development, peneliti membuat aplikasi dari bahan yang sudah dikumpulkan dari tahap design. Untuk mencoba dan melihat kegunaa produk peneiti menggunakan tahap implementasi. Hasil dari tahap evaluasi adalah 4,6; yang menunjukan bahwa aplikasi game yang dibuat layak digunakan oleh siswa sebagai materi tambahan untuk listening dalam topik describing people. Kata Kunci: Penelitian Pengembangan, Materi Listening, Mendisain materi